1996
DOI: 10.1063/1.117618
|View full text |Cite
|
Sign up to set email alerts
|

Electric field dependent EL2 capture coefficient in semi-insulating GaAs obtained from propagating high field domains

Abstract: We have determined the electric field dependence of the carrier capture coefficient of the EL2 traps in semi-insulating GaAs up to 7 kV/cm by means of the quantitative analysis of propagating high electric field domains. The experimental data show a trapping coefficient which is proportional to the electron drift velocity, supporting the microscopic model of electric field enhanced trapping of carriers over a configurational barrier.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…The quantitative measurement of the electric-field profile allows a different approach, in which we evaluate the unknown quantities, including C n (E), using the experimental electric-field distribution as the solution of the set of equations. 26 The steady-state domain apparently is a physically acceptable solution of Eqs. ͑1͒-͑4͒.…”
Section: Free and Trapped Electron Distributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantitative measurement of the electric-field profile allows a different approach, in which we evaluate the unknown quantities, including C n (E), using the experimental electric-field distribution as the solution of the set of equations. 26 The steady-state domain apparently is a physically acceptable solution of Eqs. ͑1͒-͑4͒.…”
Section: Free and Trapped Electron Distributionsmentioning
confidence: 99%
“…Thus the mechanism of a configurational barrier due to multiphonon trapping, which is found to require an electric field of only 0.5 kV/cm for the onset of electron capture, is fully consistent with our experimental results. 26 Once C n is known from the experiment over the whole field range, we have used again Eqs. ͑1͒-͑4͒ to evaluate the jϪE relation for the homogeneous electric-field distribution ͑Fig.…”
Section: Trapping Coefficientmentioning
confidence: 99%
“…This means that the best one can hope for is a qualitative agreement between the results obtained in different samples and that satisfying theories are not easily formulated. Recent experiments [3][4][5][6][7][8][9] that use the electro-optic Pockels effect in order to measure the local electric fields in the sample have opened up the way towards a more detailed quantitative understanding of the domains and the trapping process in SI GaAs. There is a considerable interest in the properties of the EL2 defect because SI GaAs has an increasing relevance, e.g., as a particle detector [10][11][12][13] and for optical data storage.…”
Section: Introductionmentioning
confidence: 99%
“…The SI features of GaAs are produced by deep level defects so that they should play a major role in the LFO, 2 and research has been carried out in order to identify its role. 3,4 In a recent study, we conducted transport measurements on SI GaAs grown by low temperature molecular beam epitaxy ͑LT-MBE͒, and we have shown that hopping conduction occurring in the impurity band of the deep level defects acts as a low propagation barrier for the high mobility free carriers in the band conduction leading to the formation of the electric-field domains due to the accumulation of charge behind the barrier. 5 This mechanism of domain formation allows us to consider, in a first approximation, that the spatial separation of two types of carriers with the slower ones at the domain front leads to the transport characteristics of the domain being dominated by its front.…”
Section: Introductionmentioning
confidence: 99%